“I should like to have my name talked of in China”: Charles Lamb, China, and Shakespeare - Dai, Yun-fang (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
Charles and Mary Lamb’s Tales from Shakespeare played an essential role in Chinese reception history of Shakespeare. The first two adaptations in China,Xiewai qitan 澥外奇譚and Yinbian yanyu 吟邊燕語, chose Tales as the source text. To figure out why the Lambs’ Tales was received in China even earlier than Shakespeare’s original texts, this paper first focuses on Lamb’s relationship with China. Based on archival materials, it then assumes that the Lambs’ Tales might have had a chance to reach China at the beginning of the nineteenth century through Thomas Manning. Finally, it argues that the decision to first bring Shakespeare to China by Tales was made under the consideration of the Lambs’ writing style, the genre choice, the similarity of the Lambs’ and Chinese audiences, and the marketability of Tales. Tracing back to the first encounter between Tales and China throws considerable light on the reception history of Shakespeare in China. It makes sense that nothing is coincidental in the history of cultural reception and the encounters have always been fundamentally influenced by efforts from both the addresser and the receptor.